If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 16 = 6z + -2 Reorder the terms: 16 + 2z = 6z + -2 Reorder the terms: 16 + 2z = -2 + 6z Solving 16 + 2z = -2 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. 16 + 2z + -6z = -2 + 6z + -6z Combine like terms: 2z + -6z = -4z 16 + -4z = -2 + 6z + -6z Combine like terms: 6z + -6z = 0 16 + -4z = -2 + 0 16 + -4z = -2 Add '-16' to each side of the equation. 16 + -16 + -4z = -2 + -16 Combine like terms: 16 + -16 = 0 0 + -4z = -2 + -16 -4z = -2 + -16 Combine like terms: -2 + -16 = -18 -4z = -18 Divide each side by '-4'. z = 4.5 Simplifying z = 4.5
| 239-3x=42x+19 | | (10x+5)(x-9)=0 | | 83-4x=41x+23 | | 123-5x=2x+18 | | (5-y)+(6-7)-(5-y)=0 | | x(4)=-6 | | t^2+17=-8t | | 71-7x=2x+20 | | 7-6x=139-37x | | 2x+3x-12x= | | 4x+8=-80-7x | | -12-4x=13-4x | | 63-2x=2x+19 | | 8x-6=7x+3 | | -31-2x=2x+19 | | q-(5-q)3=-7 | | 6x+34=15x-38 | | 2x+32=11x-58 | | 18x^3-6x^2+8x= | | 16x^2-9y^2= | | 2(x-5)=11 | | 2(x-5)=-11 | | 5*8+9-6*5=10 | | -1(6-3x)=-3 | | -5x-2(6-3x)=13 | | 8x-102=3x-7 | | 92-6x=12x+16 | | 14-9x=38-16x | | -52-7x=7x+18 | | -1(6-3x)=24 | | 6x+y=130 | | -8a-19=13 |